The disclosure practices of Shariah non-compliant income in the annual reports of Islamic banks in Malaysia - Wan A’tirah Mahyudin (Universiti Sains Islam Malaysia, 2024)
Thesis (M.A)-- Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia, 2017